Cancellation for Surfaces Revisited - Flenner, H.; Kaliman, S.; Zaidenberg, M. (Memoirs of the American Mathematical Society, 2022)
The celebrated Zariski Cancellation Problem asks as to when the existence of an isomorphism If the cancellation does not hold then